Coping Flexibility and Health-Related Quality of Life Among Older Adults: The Compensatory Effect of Co-rumination - Kroemeke, Aleksandra (Frontiers in Psychology, 2019)
Background: Coping flexibility, defined as a wide range of coping strategies, may be a promising construct in determining coping effectiveness, especially in conjunction with a person-centered approach. However, no studies have focused on these issues. The study aimed to identify the distinct, multidimensional patterns of strategies for coping with chronic health conditions and their association with changes in physical and psychological health-related quality of life (HRQoL) among older adults over a one month period. Methods: Coping strategies (brooding, reflection, co-rumination, and positive reappraisal) and HRQoL psychological and physical domains were assessed twice (at the baseline and one month later) among 210 older adults (age 76.12 ± 9.09 years, 66% women). Findings: The parallel process analysis demonstrated the sample heterogeneity regarding coping. In multidimensional latent class growth analysis (MLCGA), four coping classes of overall strategies were identified: consistently low (46%), medium and decreasing (18%), medium and increasing (20%), and consistently high (16%). The last two can be considered the coping flexibility. Participants in the medium and increasing subgroup reported enhancement in HRQoL psychological domain, whereas members of the consistently high subgroup indicated its decrease. The favorable effects were related to an increase in co-rumination. Discussion: The findings shed light on the longitudinal patterns of coping in older adults, showing that coping flexibility is more adaptive when it relies on modifying coping efforts rather than coping complexity. Co-rumination played a key role, compensated by the effect of maladaptive strategies.